Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve the equation below. What is the value of [tex]\( d \)[/tex]?

[tex]\[
\frac{3}{2}(7+3d) = 3 + 3d
\][/tex]

Steps:
1. Distribute the [tex]\(\frac{3}{2}\)[/tex] on the left side:
[tex]\[
\frac{3}{2} \cdot 7 + \frac{3}{2} \cdot 3d = 3 + 3d
\][/tex]

2. Simplify:
[tex]\[
\frac{21}{2} + \frac{9d}{2} = 3 + 3d
\][/tex]

3. Multiply through by 2 to eliminate fractions:
[tex]\[
21 + 9d = 6 + 6d
\][/tex]

4. Solve for [tex]\( d \)[/tex]:
[tex]\[
21 + 9d = 6 + 6d \\
21 - 6 = 6d - 9d \\
15 = -3d \\
d = -5
\][/tex]

Therefore, the value of [tex]\( d \)[/tex] is [tex]\( -5 \)[/tex].


Sagot :

To solve the given equation for [tex]\( d \)[/tex], we can proceed as follows:

[tex]\[ \frac{3}{2}(7+3d) = 3 + 3d \][/tex]

First, we distribute the [tex]\( \frac{3}{2} \)[/tex] on the left side of the equation:

[tex]\[ \frac{3}{2} \cdot (7 + 3d) = \frac{3}{2} \cdot 7 + \frac{3}{2} \cdot 3d = \frac{21}{2} + \frac{9d}{2} \][/tex]

Thus, the equation now looks like:

[tex]\[ \frac{21}{2} + \frac{9d}{2} = 3 + 3d \][/tex]

Next, to eliminate the fractions, we multiply every term in the equation by 2:

[tex]\[ 2 \cdot \left( \frac{21}{2} + \frac{9d}{2} \right) = 2 \cdot 3 + 2 \cdot 3d \][/tex]

This simplifies to:

[tex]\[ 21 + 9d = 6 + 6d \][/tex]

Now, we have a linear equation:

[tex]\[ 21 + 9d = 6 + 6d \][/tex]

To solve for [tex]\( d \)[/tex], we first get all the [tex]\( d \)[/tex]-terms on one side and the constants on the other side. Subtract [tex]\( 6d \)[/tex] from both sides:

[tex]\[ 21 + 9d - 6d = 6 + 6d - 6d \][/tex]

This simplifies to:

[tex]\[ 21 + 3d = 6 \][/tex]

Next, we isolate the term with [tex]\( d \)[/tex] by subtracting 21 from both sides:

[tex]\[ 3d = 6 - 21 \][/tex]

[tex]\[ 3d = -15 \][/tex]

Finally, we solve for [tex]\( d \)[/tex] by dividing both sides by 3:

[tex]\[ d = \frac{-15}{3} \][/tex]

[tex]\[ d = -5 \][/tex]

So, the value of [tex]\( d \)[/tex] is:

[tex]\[ d = -5 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.